2017
DOI: 10.32890/ijms.25.1.2018.10496
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Mediating Effect of Strategic Agility in the Relationship Between Intellectual Capital and Organizational Excellence in Jordan Service

Abstract: This study aims to investigate the effect of intellectual capital and strategic agility on organizational excellence in service sector of Jordan. A total of 550 questionnaires were collected from respondents who were chosen from a stratified random sampling. The results revial that intellectual capital and its dimensions, human capital, structural capital, and relational capital, have a significant impact on strategic agility as well as organizational excellence. Moreover, results reveal that strategic agility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Other researchers have empirically studied strategic agility using the three Doz and Kosonen (2008a) dimensions (Al-Azzam et al , 2017; Clauss et al , 2019; Junni et al , 2015; Ofoegbu and Akanbi, 2012). However, this study is the first to operationalize the construct using the 15 subfactors identified by Doz and Kosonen (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have empirically studied strategic agility using the three Doz and Kosonen (2008a) dimensions (Al-Azzam et al , 2017; Clauss et al , 2019; Junni et al , 2015; Ofoegbu and Akanbi, 2012). However, this study is the first to operationalize the construct using the 15 subfactors identified by Doz and Kosonen (2010).…”
Section: Discussionmentioning
confidence: 99%
“…The service sector of Jordan is the overarching sector as compared to others; it contributes to 67% of GDP while the contribution of others is merely 33% (Al-Azzam et al , 2017). Despite its dominance, this sector is facing several problems, and the most important one is the organizational performance of service firms.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of questionnaires was made possible by post and e-mail. This was followed by phone calls to ensure adequate response (as informed by Salawudeen, 2021;Al-Azzam et al, 2018;Bakar et al, 1985) from the shareholders utilizing the questionnaire.…”
Section: Methodsmentioning
confidence: 99%